Evaluation of substrate metabolism in critically ill pediatric patients - Antonius H Pudjiadi, Nurnaningsih (Universitas Gadjah Mada, 2008)
Background: Critically ill pediatric patients are characterized by a hypermetabolic state, a catabolic response, and a decreased capacity to utilize substrate. Metabolic state of critically ill pediatric patients can be detected by analyzing substrate utilization.Objective: To determine the metabolic state of critically ill pediatric patients using PRISM III Score, blood glucose level, and urinary nitrogen excretion.Methods: A cross sectional study was conducted in Pediatric Intensive Care Unit (PICU) of Cipto Mangunkusumo Hospital Jakarta between May and September 2006. All admitted PICU patients, except those with renal or hepatic failure, burns, diabetic ketoacidosis and died in the first 24 hours, were included. PRISM III Scores were measured in the first 24-hours of admission. Blood glucose level was observed at random within the first hour of hospitalization, while urinary nitrogen excretion was measured using urine collected in the second 24-hours of admission.Results: Fifteen cases were eligible for this study. Their age ranged between 1 to 96 months. The median (01 ;03) for PRISM III Scores, random blood glucose, and urinary nitrogen excretion were 6.0 (3.0;11.0), 123.0 (100.0;227.0), and 279.4 (124.3;408.4) mg/dL, respectively. There were no significant correlations between PRISM III Scores and random blood glucose (r=0.40;p=0.14), and between PRISM III Scores and urinary nitrogen excretion (r = -0.27;p = 0.33). There was significant correlation between random blood glucose and urinary nitrogen excretion (r=0.56;p=0.03).Conclusion: Critically ill pediatric patients had a catabolic state that had no association with PRISM III Scores. Random blood glucose level within the first hour of admission predicted the increasing protein catabolism.Key words: critically ill pediatric patients - blood glucose level - urinary nitrogen excretion - PRISM III Score.